1999
DOI: 10.1103/physrevd.59.075006
|View full text |Cite
|
Sign up to set email alerts
|

Bilepton production at hadron colliders

Abstract: We examine, as model-independently as possible, the production of bileptons at hadron colliders. When a particular model is necessary or useful, we choose the 3-3-1 model. We consider a variety of processes:, where Y and φ are vector and scalar bileptons, respectively. Given the present low-energy constraints, we find that at the Tevatron, vector bileptons are unobservable, while light scalar bileptons (M φ < ∼ 300 GeV) are just barely observable. At the LHC, the reach is extended considerably: vector bilepton… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
98
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 23 publications
1
98
0
Order By: Relevance
“…Another striking feature of models with complex isospin-triplets, such as the GM model, the left-right symmetric model, the littlest Higgs model, and some models motivated by neutrino masses, is the appearance of doublycharged states H ±± . At hadron colliders, such doubly-charged Higgs bosons are studied via the pair production mechanism [10,32,33] as well as the single production mechanism [33,34] and the W -boson fusion mechanism [6,35]. They can also be investigated at the ILC and its e − e − , e − γ and γγ option in various scenarios [36].…”
Section: Georgi-machacek Modelmentioning
confidence: 99%
“…Another striking feature of models with complex isospin-triplets, such as the GM model, the left-right symmetric model, the littlest Higgs model, and some models motivated by neutrino masses, is the appearance of doublycharged states H ±± . At hadron colliders, such doubly-charged Higgs bosons are studied via the pair production mechanism [10,32,33] as well as the single production mechanism [33,34] and the W -boson fusion mechanism [6,35]. They can also be investigated at the ILC and its e − e − , e − γ and γγ option in various scenarios [36].…”
Section: Georgi-machacek Modelmentioning
confidence: 99%
“…In the case of the double-charged scalar-bilepton, CDF and DØ establish the lower bound for the bilepton mass in the range 110 − 150 GeV [15,16,17,18] with 95% C.L., from the exclusive bilepton decay into left-handed eτ , µ τ and µ µ pairs by considering the left-right model, the SM with a Higgs triplet and the little Higgs model. The study of vector-bilepton pair production from the hadron collider cannot be completely model independent because the SM Drell-Yan process violates unitarity, then requiring extra s− and t−channel contributions from new neutral gauge boson and from exotic fermions [19]. Having this in mind and in order to focus the LHC physics, we do elect a model to get correct unitarity behavior for bilepton pair production in a p p collider.…”
Section: Introductionmentioning
confidence: 99%
“…This could lead to a natural explanation of the unbalancing heavy top quarks in the fermion mass hierarchy [7]. Recent analyses have indicated that signals of new particles in this model, bileptons [8] and exotic quarks [9] may be observed at the Tevatron and the Large Hadron Collider (LHC).…”
Section: Introductionmentioning
confidence: 99%